Exploring pre-service visual art teachers’ competitiveness through porter’s five forces model - Koshkinbayeva, Nurgul; Shagataeva, Zaure; Utepova, Almagul; Taukebayeva, Kunsulu; Kurmantayeva, Sulugul (Journal of Education and e-Learning Research, 2023)
The primary objective of this cross-sectional study was to explore the degree to which 117 pre-service visual art teachers’ competitiveness within the education field. A self-reported competitiveness scale (six items distributed between three factors) was designed and validated by the authors based on the focal points of Michael Porter’s Five Forces framework. Additionally, the respondents’ digital competence was assessed as an auxiliary criterion of educator attractiveness in the art education domain. Both competitiveness and digital skills measurements yielded mediocre scores. Regression analysis showed that respondents’ competitiveness perceptions were predicted neither by digital skills level nor by socio-demographic characteristics such as age, gender, rural or urban background, marital status or whether the student was a graduate or undergraduate. The present study highlights the need for understanding of how visual art majors perceive the sector and evaluate competitiveness among visual art students which itself indicates its sizable contribution to educational research. Other researchers can employ the competitiveness questionnaire introduced to gain deeper insights into the topic or related subjects.